Variation of electron density before large earthquakes in Southeast Asia observed by CHAMP satellite from 2004 to 2009 - N A Mohamad Rizal; S H Md Yusof; Nurul Shazana Abdul Hamid; Idahwati Sarudin (Penerbit Universiti Kebangsaan Malaysia, 2020)
This project studies the behaviour of the pre-earthquake (EQ) ionospheric parameter by analysing the variation of electron density (Ne) measured by the CHAMP satellite, which is one of the satellites that collect in-situ data of Ne in the ionosphere. Data from two weeks before the main shock of an EQ are analysed to observe the pattern behaviour of the Ne before the EQs. Monitoring this parameter is one of the methods of observing the ionosphere for studying EQ precursors. The area of focus in this study is the Southeast Asian region, where EQs happen frequently. This study involves large EQs with a magnitude >7.5 that occurred within five years from 2004 until 2009. Significant anomalous behaviour of Ne was identified within 14 days prior to the EQs.